2021
DOI: 10.1186/s13063-020-04961-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture for sciatica: study protocol for a randomized controlled pilot trial

Abstract: Background Acupuncture is widely used for pain diseases while evidence of its efficacy for sciatica is insufficient. We aim to explore the feasibility and efficacy of acupuncture with different acupoint selecting strategies for sciatica induced by lumbar disc herniation. Methods This is a multicenter, three-arm, patient-assessor-blinded randomized controlled pilot trial. Ninety patients will be assigned randomly into 3 groups including disease-affe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The effectiveness of acupuncture was better than the sham and no acupuncture group, alleviating the pain cannot be elucidated by the placebo effect barely [ 37 ]. It can also be found that acupuncture in different acupoints has a positive analgesic efficacy on sciatica treatment, and the effectiveness is better than the sham acupuncture group [ 38 ]. In alleviation of knee osteoarthritis (KOA), acupuncture has a noticeable higher cure rate than sham acupuncture, it is worth mentioning that over time, the utility of EA seems to be higher than other control groups [ 39 ].…”
Section: Clinical Research Condition Of Acupuncture Analgesiamentioning
confidence: 99%
“…The effectiveness of acupuncture was better than the sham and no acupuncture group, alleviating the pain cannot be elucidated by the placebo effect barely [ 37 ]. It can also be found that acupuncture in different acupoints has a positive analgesic efficacy on sciatica treatment, and the effectiveness is better than the sham acupuncture group [ 38 ]. In alleviation of knee osteoarthritis (KOA), acupuncture has a noticeable higher cure rate than sham acupuncture, it is worth mentioning that over time, the utility of EA seems to be higher than other control groups [ 39 ].…”
Section: Clinical Research Condition Of Acupuncture Analgesiamentioning
confidence: 99%
“…Treatment offered in this trial is developed by experts and refer to our pilot study. 23 Report of the intervention is following the Standards for Reporting Interventions in Clinical Trials of Acupuncture guidelines with details shown in table 1 and figure 2. 24 Celebrex (Pfizer Pharmaceutical) may be prescribed for those with unbearable pain as rescue medicine, based on their needs.…”
Section: Interventionmentioning
confidence: 99%
“…The increase of ROS expression leads to the increase of TNF-α, IL-1β and IL-6, and inflammatory factors are important key factors in the pathophysiological mechanism of sciatica [15] [16]. At present, acupuncture and moxibustion are commonly used in the clinical treatment of nerve pain [17], which has been proven to be an effective and safe treatment in clinical practice, and has achieved good results in reducing pain and improving patients' quality of life [18] [19] [20]. Acupuncture and moxibustion, with their low price, and quick effect, can be combined with other treatment methods, and the incidence of adverse reactions after treatment is low, so it has become the choice of routine treatment for sciatica [20].…”
Section: Introductionmentioning
confidence: 99%